Approach to Pediatric Emergency - Jaydeep Choudhury; Jayanta Bandyopadhyay (India : Jaypee Brothers Medical Publishers, 2011)
Approach to Pediatric Emergency is practical approach-based, algorithmic and naturally ready to use. This "at a glance" format can be accessed by emergency physicians, emergency fellows, trainees, pediatric postgraduates and even practicing pediatricians.
Table of Contents Section 1: General emergency Section 2: Resuscitation Section 3: Sedation, Analgesia, Intubation and Procedures Section 4: Neonatal Emergencies Section 5: Respiratory Emergencies Section 6: Cardiovascular Emergencies Section 7: Gastrointestinal Emergencies Section 8: Renal Emergencies Section 9: Neurological Emergencies Section 10: Hematological Emergencies Section 11: Endocrinal Emergencies Section 12: Environmental Problems Section 13: Poisoning Section 14: Foreign Body Section 15: Psychiatric Behavioral and Social Issues Section 16: Trauma and Orthopedics Section 17: Opthalmological Emergencies Section 18: Otolaryngological Emergencies Section 19: Dermatological Emergencies Section 20: Infections Section 21: Miscellaneous Emergencies Section 22: Medicolegal Issues
Incluye Table of contents
Incluye Table of Appendix
Keywords: PEDIATRICS -- EMERGENCY; PEDIATRÍA -- EMERGENCIAS